Light sensitivity within areas of geographic atrophy secondary to age-related macular degeneration - Pfau, M; von der Emde, L; Dysli, C; Thiele, S; Möller, PT; Lindner, M; Nadal, J; Schmid, M; Schmitz-Valckenberg, S; Holz, FG; Fleckenstein, M (Association for Research in Vision and Ophthalmology, 2019)
Purpose: To investigate residual sensitivity within geographic atrophy (GA) secondary to age-related macular degeneration.